Peran PPATK Dalam Mengungkap Tindak Pidana Pencucian Uang Hasil Dari Tindak Pidana Korupsi - Fitriana, Firzatul Rima; Daim, Nuryanto A. (Law and Humanity, 2025)
The Financial Transaction Reports and Analysis Center (PPATK) plays a strategic role in uncovering money laundering crimes (TPPU) originating from corruption offenses (tipikor) in Indonesia. As a financial intelligence institution, PPATK is responsible for detecting, analyzing, and reporting suspicious financial transactions often used to obscure the proceeds of corruption. This article explores PPATK's role within the domestic context, including the receipt and analysis of suspicious transaction reports (STRs), tracing the flow of illicit funds from corruption, and coordinating with law enforcement and relevant national agencies. The main challenges faced by PPATK include low compliance in reporting by financial institutions, limited access to specific transaction data, and gaps in regulatory implementation. Through policy analysis and domestic case studies, this article emphasizes the importance of strengthening PPATK's capacity by optimizing technology, enhancing regulations, and fostering inter-agency cooperation at the national level. These efforts are expected to support the creation of a more transparent and accountable financial system in Indonesia.